STUDI KONSEP DAN BENTUK KARYA SENI RUPA MURNI MODERN INDONESIA YANG TERINSPIRASI SENI TRADISI NUSANTARA - Purnomo, Tonny (Institut Seni Indoensia Surakarta, 2016)
This study aims to explain the concepts and forms of modern works of pure art that is inspired by nusantara traditional arts. The nusantara traditional art, here, not on geographical constraints but in cultural areas. This particular study, the research area is the Yogyakarta and Surakarta. This study also continued to restrict and emphasis on the works of pure art, especially modern art that is inspired by the art of Javanese tradition, but did not rule on the works of art inspired by the nusantara traditional arts other than Java. This study uses the aesthetic approach of Clive Bell confirms the significant form. The analysis is the interpretation of the analysis applied to give appreciation to the concepts and art forms that become the object of research. This study takes an object of art created by I Gusti Nurata Nengah, Heri Dono, and Soegeng Toekio. The findings produced is the concept and form of the works of modern art that is inspired by the Nusantara traditional art not necessarily present because the influence of the trend alone, but is the result of a personal experience that in regard to the events in the life of the natural and social environment, and manifested in personal expression in line with experience aesthetic inspired by the concept and the traditional art form experienced and understood. The forms were present were not 100% like in the traditional arts, but still feels inspiring visual character of locality tradition, both in terms of technique, color or deformationof the display. Forms of the puppets and wayang beber be one option is a reference in the visual reinterpreting the tradition art references terkair especially its art.Keywords: pure visual arts, concept, form, nusantara traditional art.